Organizational Culture of HEIs: What matters the most? - DR. ANJUM IHSAN; ABID AHMAD; DR. FAYYAZ ALI SHAH; HAMID ULLAH (Journal of Business & Tourism, 2021)
Culture and climate of an organization is valued to gain competitive advantage in today’s modern organizations. This study aimed to analyze the relative importance of Artifacts, Espoused Beliefs & Values and Basic Underlying Assumptions—the constituents of organization culture in relation to organization performance in Higher Education Institutes (HEIs) of district Peshawar. Cross-sectional data was collected from 250 employees of public and private sector universities working in drade-17 or above as teaching faculty or administrative staff using multi-stage cluster sampling technique. Findings indicated strong impact of constituents of organization cultural on organization performance and that the artifacts component has greater impact on organization performance than the other two components. Espoused beliefs and values have smaller impact than artifacts but greater impact than basic underlying assumptions and basic underlying assumptions have smallest impact. Thus leadership and management of HEIs should pay more and more attention to their tangible artifacts and making then more and more visible and ensuring their proper usage as this will lead to improvement in organization performance.